Genetic Diversity and Phylogeography of Thottapalayam thottimvirus (Hantaviridae) in Asian House Shrew (Suncus murinus) in Eurasia - Kikuchi, Fuka; Aoki, Keita; Ohdachi, Satoshi D.; Tsuchiya, Kimiyuki; Motokawa, Masaharu; Jogahara, Takamichi; Sơn, Nguyễn Trường; Bawm, Saw; Lin, Kyaw San; Thwe, Thida Lay; Gamage, Chandika D.; Ranorosoa, Marie Claudine; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Murid and cricetid rodents were previously believed to be the principal reservoir hosts of hantaviruses. Recently, however, multiple newfound hantaviruses have been discovered in shrews, moles, and bats, suggesting a complex evolutionary history. Little is known about the genetic diversity and geographic distribution of the prototype shrew-borne hantavirus, Thottapalayam thottimvirus (TPMV), carried by the Asian house shrew (Suncus murinus), which is widespread in Asia, Africa, and the Middle East. Comparison of TPMV genomic sequences from two Asian house shrews captured in Myanmar and Pakistan with TPMV strains in GenBank revealed that the Myanmar TPMV strain (H2763) was closely related to the prototype TPMV strain (VRC66412) from India. In the L-segment tree, on the other hand, the Pakistan TPMV strain (PK3629) appeared to be the most divergent, followed by TPMV strains from Nepal, then the Indian-Myanmar strains, and finally TPMV strains from China. The Myanmar strain of TPMV showed sequence similarity of 79.3–96.1% at the nucleotide level, but the deduced amino acid sequences showed a high degree of conservation of more than 94% with TPMV strains from Nepal, India, Pakistan, and China. Cophylogenetic analysis of host cytochrome b and TPMV strains suggested that the Pakistan TPMV strain was mismatched. Phylogenetic trees, based on host cytochrome b and cytochrome c oxidase subunit I genes of mitochondrial DNA, and on host recombination activating gene 1 of nuclear DNA, suggested that the Asian house shrew and Asian highland shrew (Suncus montanus) comprised a species complex. Overall, the geographic-specific clustering of TPMV strains in Asian countries suggested local host-specific adaptation. Additional in-depth studies are warranted to ascertain if TPMV originated in Asian house shrews on the Indian subcontinent.